PERANTI KOHESI DALAM KARANGAN SISWA SMP - Titis Mawarti (Program Pascasarjana Universitas Islam Darul `Ulum Lamongan, 2014)
The composition of SMP students belong to language unit called discourse. Good discourse uses cohesion instrument as the unifer of the discourse. Therefore, it is urgently needed to research the instrument of cohesion in composition of SMP students. The objective of the research is to describe the instrument of cohesion including lexical and grammtical cohesion instruments found in the composition of the seventh year students of SMP Negeri 5 Tuban academic year 2012/2013. The research uses descriptive-qualitative method. Source of data are taken from the composition of the seventh year students of SMP Negeri 5 Tuban academic year 2012/2013. In collecting data, the researsher uses the techniques of test, attentive observation of the instrument and data corpus sheets. The result of the research shows that in writing the composition, the students of SMP use cohesion instruments lexikally like repetition, synonym, antonym, hyponim, collocation and equivalence; and grammatically like reference, substitution, elleptic and conjunction.